THE DYNAMICS OF THOUGHT AND POLICY OF CLASSIFICATION OF SCIENCES IN INDONESIAN ISLAMIC RELIGIOUS COLLEGES - Muhamad Sabirin; Muhammad Zainal Abidin; Muhammad Taufik (UIN Antasari Banjarmasin, 2022)
The idea of the classification of science in Islamic Religious Colleges in Indonesia can be traced historically from the spirit of the establishment of Islamic tertiary institutions in this country, which from time to time transformed dynamically to find the ideal format of sciences. The spirit of the classification of science is basically related to efforts to bring up integralistic sciences, which no longer focuses solely on the pure religious sciences, but also accommodates general sciences. The writing of this paper uses a combination of library research and field research. The aspect of the literature to be investigated is about the policies of the Indonesian government related to the classification of science in Islamic tertiary institutions in Indonesia. In the implementation aspect, it took place in three campuses: UIN Syarif Hidayatullah Jakarta, UIN Sunan Kalijaga Yogyakarta and UIN Maliki Malang. An important finding from this research is that the implementation of the policy on science sciences at Islamic Religious Colleges in Indonesia is not completely smooth sailing. Strong resistance from below on the spirit of uniformity of nomenclature turned out to have an impact on the revocation of Minister of Religion Regulation No. 36/2009 concerning Determination of Science and Academic Degrees in the Environment of Religious Higher Education. Finally, PMA 33 Year 2016 no longer talks about the uniformity of faculty nomenclature, this regulation only talks about the names of study programs and academic degrees that are obtained Gagasan klasifikasi ilmu di Perguruan Tinggi Agama Islam di Indonesia dapat ditelusuri secara historis dari semangat berdirinya perguruan tinggi Islam di negeri ini dalam kurun waktu yang panjang, yang dari waktu ke waktu terus mengalami transformasi dinamis untuk menemukan formatnya yang ideal. Semangat pengklasifikasian ilmu pada dasarnya terkait dengan upaya memunculkan ilmu-ilmu integralistik, yang tidak lagi hanya menitikberatkan pada ilmu-ilmu agama murni, tetapi juga mengakomodir ilmu-ilmu umum. Penulisan artikel ini memadukan antara studi kepustakaan dan penelitian lapangan. Aspek literatur yang akan diteliti adalah tentang kebijakan pemerintah Indonesia terkait klasifikasi ilmu di perguruan tinggi Islam di Indonesia, dengan lokus penelitian pada tiga kampus utama, yaitu UIN Syarif Hidayatullah Jakarta, UIN Sunan Kalijaga Yogyakarta dan UIN Maliki Malang. Temuan penting dari penelitian ini adalah bahwa implementasi kebijakan ilmu sains di Perguruan Tinggi Agama Islam di Indonesia tidak sepenuhnya berjalan mulus. Resistensi yang kuat dari bawah terhadap semangat penyeragaman nomenklatur ternyata berdampak pada pencabutan Peraturan Menteri Agama No. 36 Tahun 2009 tentang Penetapan Gelar Keilmuan dan Akademik di Lingkungan Perguruan Tinggi Keagamaan. Terakhir, PMA 33 Tahun 2016 tidak lagi membicarakan keseragaman nomenklatur fakultas, peraturan ini hanya membicarakan nama program studi dan gelar akademik yang diperoleh